Hypercodification de la Common Law: en quête de sens - Wagner, Anne (HERMES - Journal of Language and Communication in Business, 2005)
Law is, by deﬁnition, the codiﬁcation of modes of expression in a given society. However, its use is distinctive owing to the ways in which users apply or modify it. The shift in meaning between the product and its expression can be analysed not only within its content but also by the means of communication employed. The inﬂuence of spheres from intermediary competences, such as Administration and the Legal Profession is one of the main issues to explore. The linguist’s analysis cannot be limited to language, but should also integrate corporal and sign communication. These interferences are the conveyors of a derived creation and are distinctive from written law countries to common law countries. My paper will focus on the modes of expression in English Law with a view to showing common and original features.